hnRNPA2B1 represses the disassembly of arsenite-induced stress granules and is essential for male fertility - Xiaoli Wang; Xu Fan; Jin Zhang; Fengli Wang; Jingshou Chen; Yujiao Wen; Lingjuan Wang; Tao Li; Huaibiao Li; Heng Gu; Youzhi Zhang; Shuiqiao Yuan (Cell Reports, 2024)
Summary: Although the composition and assembly of stress granules (SGs) are well understood, the molecular mechanisms underlying SG disassembly remain unclear. Here, we identify that heterogeneous nuclear ribonucleoprotein A2/B1 (hnRNPA2B1) is associated with SGs and that its absence specifically enhances the disassembly of arsenite-induced SGs depending on the ubiquitination-proteasome system but not the autophagy pathway. hnRNPA2B1 interacts with many core SG proteins, including G3BP1, G3BP2, USP10, and Caprin-1; USP10 can deubiquitinate G3BP1; and hnRNPA2B1 depletion attenuates the G3BP1-USP10/Caprin-1 interaction but elevates the G3BP1 ubiquitination level under arsenite treatment. Moreover, the disease-causing mutation FUSR521C also disassembles faster from SGs in HNRNPA2B1 mutant cells. Furthermore, knockout of hnRNPA2B1 in mice leads to Sertoli cell-only syndrome (SCOS), causing complete male infertility. Consistent with this, arsenite-induced SGs disassemble faster in Hnrnpa2b1 knockout (KO) mouse Sertoli cells as well. These findings reveal the essential roles of hnRNPA2B1 in regulating SG disassembly and male mouse fertility.